Obesity-induced tissue free radical generation: An in vivo immuno-spin trapping study - Khoo, Nicholas K.H. (2012)
Assessment of tissue free radical production is routinely accomplished by measuring secondary by-products of redox reactions and/or diminution of key antioxidants such as reduced thiols. However, immuno-spin trapping, a newly developed immunohistochemical technique for detection of free radical formation, is garnering considerable interest as it allows for the visualization of 5, 5-dimethyl-1-pyrroline N-oxide (DMPO)-adducted molecules. Yet, to date, immuno-spin trapping reports have utilized in vivo models in which successful detection of free radical adducts required exposure to lethal levels of oxidative stress not reflective of chronic inflammatory disease. To study the extents and anatomic locations of more clinically relevant levels of radical formation, we examined tissues from high-fat (HF) diet-fed mice, a model of low-grade chronic inflammation known to demonstrate enhanced rates of reactive species production. Mice subjected to 20 weeks of HF diet displayed increased free radical formation (anti-DMPO mean fluorescence staining) in skeletal muscle (0.863 ± 0.06 units vs 0.512 ± 0.07 units), kidney (0.076 ± 0.0036 vs 0.043 ± 0.0025), and liver (0.275 ± 0.012 vs 0.135 ± 0.014) compared to control mice fed normal laboratory chow (NC). Western blot analysis of tissue homogenates confirmed these results showing enhanced DMPO immunoreactivity in HF mice compared to NC samples. The obesity-related results were confirmed in a rat model of pulmonary hypertension and right heart failure in which intense immunodetectable radical formation was observed in the lung and right ventricle of monocrotaline-treated rats compared to saline-treated controls. Combined, these data affirm the utility of immuno-spin trapping as a tool for in vivo assessment of altered extents of macromolecule oxidation to radical intermediates under chronic inflammatory conditions.